THE ROLE OF BAKUDAPA TUAGAMA IN ROAD INFRASTRUCTURE DEVELOPMENT: A STUDY OF NENIARI GUNUNG VILLAGE, TANIWEL DISTRICT, WEST SERAM REGENCY - Mersye Heumase; Aholiab Watloly; Pieter Jacob Pelupessy; Jeffry EM Leiwakabessy (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study examines the role of church advocacy in addressing social inequality related to road infrastructure development in Neniari Gunung Village, a disadvantaged area in West Seram Regency, Indonesia. Using a qualitative case study approach, data were collected through in-depth interviews, observation, and document analysis. The findings reveal that inadequate road infrastructure has significantly affected education, healthcare access, and local economic activities. In response to weak government accountability and alleged budget mismanagement, the church emerged as a moral and social actor advocating for justice and transparency. Through persuasive engagement, community mobilization, and dialogue with authorities, church advocacy strengthened social awareness, participation, and solidarity within the village. Although tangible infrastructure improvements remain limited, the advocacy process contributed to empowering marginalized communities and sustaining public discourse on equitable development. The study highlights the importance of faith-based institutions as informal governance actors capable of influencing development processes in disadvantaged regions.